Supporting Students with Diverse Learning Needs Using Universal Design for Learning in Online Learning: Voice of the Students - Montgomery, Diane P.; Snow, Kathy (Journal of Teaching and Learning, 2024)
During the COVID-19 pandemic, online learning became the predominant mode of learning for 33 to 54% of students in Canada’s three largest school boards. As inclusive practices continue to grow and online learning is now part of the Ontario curriculum, educators need guidance on how to support K-12 students with diverse learning needs in online and inclusive classrooms. This case study attends to the voice of elementary and high-school students, with and without disabilities who shared their experiences of online learning during the pandemic. It explored the impacts of integrating multiple methods of instruction, assessment, and technology to accommodate diverse learning needs. Results indicated that limited opportunity for connections and lack of structure and guidance were key factors that impacted the students’ motivation and ability to learn in the online environment, and age was a determining factor in technology use preferences.